2016
DOI: 10.31235/osf.io/7c4wv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Black are Lakisha and Jamal? Racial Perceptions from Names Used in Correspondence Audit Studies

Abstract: Online correspondence audit studies have emerged as the primary method to examine racial discrimination. Although audits use distinctive names to signal race, few studies scientifically examine data regarding the perception of race from names. Different names treated as black or white may be perceived in heterogeneous ways. I conduct a survey experiment that asks respondents to identify the race they associate with a series of names. I alter the first names given to each respondent and inclusion of last names.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(157 citation statements)
references
References 22 publications
2
153
2
Order By: Relevance
“…In this context, we directly signaled race by selecting either “Black or African American” or “White,” although we could not directly observe how it was used in their deliberations. Importantly for our purposes, the names of our testers were not particularly indicative of a specific race group and were unlikely to convey significant race signals on their own (see where we followed the guidance of Gaddis []), so we randomly assigned race to each tester pair–college combination regardless of the actual race of participants. That is, the same tester pairs both checked “White” at one subsample of colleges and both checked “Black” at another subsample of colleges.…”
Section: Design and Approachmentioning
confidence: 99%
“…In this context, we directly signaled race by selecting either “Black or African American” or “White,” although we could not directly observe how it was used in their deliberations. Importantly for our purposes, the names of our testers were not particularly indicative of a specific race group and were unlikely to convey significant race signals on their own (see where we followed the guidance of Gaddis []), so we randomly assigned race to each tester pair–college combination regardless of the actual race of participants. That is, the same tester pairs both checked “White” at one subsample of colleges and both checked “Black” at another subsample of colleges.…”
Section: Design and Approachmentioning
confidence: 99%
“…Further, it is customary to include letters of reference from previous employers and, importantly, a photograph of the applicant. The photo requirement makes it possible to signal racial phenotype directly rather than using the indirect and imprecise signal of typical minority names (see Gaddis 2017).…”
Section: Samplementioning
confidence: 99%
“…In fact, several studies find that uncommon and Black-sounding names are most frequently given by mothers with low levels of education (Fryer and Levitt, 2004;Lieberson and Bell, 1992). Gaddis (2017) found that Black names were perceived as more Black when the mother had a lower educational level, compared to a higher educational level. Black names given by highly educated mothers were less likely to be perceived as indicating Blackness (Gaddis, 2017).…”
Section: Race In the United States Is Confounded With Social Classmentioning
confidence: 99%